2003
DOI: 10.1002/bem.10083
|View full text |Cite
|
Sign up to set email alerts
|

Whole body exposure of rats to microwaves emitted from a cell phone does not affect the testes

Abstract: The objective of this study was to investigate the effects of radiofrequency radiation emitted from cellular phones on the lipid composition, malondialdehyde concentration, p53 immune reactivity, sperm count, morphology, histological structure of testes, and on rectal temperature of rats exposed to microwave radiation emitted from cellular phones. Sixteen Spraque-Dawley rats were separated into two groups of eight, sham exposed (control) and experimental. The rats were confined in plexiglas cages specially des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 41 publications
6
98
1
7
Order By: Relevance
“…5,6 Recent studies showed the negative effect of MPs on the male genital system, both in animals 7,8 and in human subjects. 9 All these studies dealt only with the influence of MPs on testicular structure and function 7,[9][10][11] and male accessory genital organs. 8 However, no studies to date have analyzed the potential effect of exposure to EMWs emitted from MPs on male sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Recent studies showed the negative effect of MPs on the male genital system, both in animals 7,8 and in human subjects. 9 All these studies dealt only with the influence of MPs on testicular structure and function 7,[9][10][11] and male accessory genital organs. 8 However, no studies to date have analyzed the potential effect of exposure to EMWs emitted from MPs on male sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Araştırmaların bir grubu cep telefonu kaynaklı radyasyonun biyolojik sistemlerde olumsuz etkiye neden olmadığı yönündeyken, bir grubu ise özellikle üreme sisteminde çeşitli olumsuzluklara neden olduğunu vurgulamaktadır [3,4,15,16]. 2003 yılında Dasdağ ve arkadaşları sıçanlar ile yaptıkları çalışmalarında 890-915 MHz cep telefonunu radyasyonunun 1 ay ve günde 20 dakikalık uygulanmasının sperm sayısında, yapısında ve seminifer tübül çaplarında, gruplar arasında anlamlı bir farka neden olmadığını gözlemlemişlerdir [3].…”
Section: Discussionunclassified
“…Araştırmaların bir grubu cep telefonu kaynaklı radyasyonun biyolojik sistemlerde olumsuz etkiye neden olmadığı yönündeyken, bir grubu ise özellikle üreme sisteminde çeşitli olumsuzluklara neden olduğunu vurgulamaktadır [3,4,15,16]. 2003 yılında Dasdağ ve arkadaşları sıçanlar ile yaptıkları çalışmalarında 890-915 MHz cep telefonunu radyasyonunun 1 ay ve günde 20 dakikalık uygulanmasının sperm sayısında, yapısında ve seminifer tübül çaplarında, gruplar arasında anlamlı bir farka neden olmadığını gözlemlemişlerdir [3]. Aynı araştırmacılar benzer dozda cep telefonu radyasyonunun uzun dönem etkisini inceledikleri diğer bir çalışmalarında sıçanları 10 ay süresince, haftada 7 gün ve günde 2 saat radyofrekans dalgalarının etkisine bırakmışlar ve uzun dönem cep telefonunun ürettiği radyofrekans dalgalarına etkin kalmanın da sıçanlarda spermiyogenezisi etkilemediğini bildirmişlerdir [15].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…An animal study by Dasdag et al on rats that were exposed to mobile phone for 20 minutes a day for 1 month with a distance of 0.5 cm has produced insignificant result and that there is no proof of the side effects on the histology of testes, immune re-activation of p53, number of sperm, morphology of sperm, malondialdehyde concentration, and diameter of testical seminifrous tubule [18].…”
Section: H H Syam Et Almentioning
confidence: 99%